Characteristics of the successful 21st century information professional - Heye, Dennie; ScienceDirect eBooks (Oxford [England] : Chandos Publications, 2006)
This book is intended for professional Library and Information Services (LIS) staff and LIS students who want to be more successful as information professionals. The LIS profession is one of the most challenging in the 21st century, combining expertise in information management with information technology skills and knowledge of marketing. The author has written a practical and concise book on key characteristics, with practical tips and techniques. Characteristics of the Successful 21st Century Information Professional is a guide to the diverse characteristics of the information professional, helping readers to achieve greater success in their jobs and careers.
Introduction -- You are creative and keen to innovate -- You are a search engine guru -- You see the big picture -- You maintain a healthy work-life balance -- You show leadership -- You can persuade others -- You are an effective networker -- You know how you can add value -- You have effective presentation skills -- You know how to measure value -- You manage your time and use the magical word 'no' -- You know the basics of information architecture -- You speak the technical jargon -- You can manage a project You know how to effectively market yourself -- You are always up to date -- conclusion.
Includes bibliographical references (pages 163-164) and index.
Elsevier
Keywords: Information scientists; LANGUAGE ARTS & DISCIPLINES -- Library & Information Science -- General; Information scientists; Electronic books